An example analysis of the effect of different obstacle-surmounting modes on take-off performance - CHEN Hongying; XU Mengyu; NI Maolin (Hangkong gongcheng jinzhan)
In operation of civil aircraft，the maximum take-off weight is limited by the performance when one engine fails，and it is of great significance to optimize take-off performance by executing different obstacle-surmounting methods to increase the maximum take-off weight. Based on the theoretical analysis of the take-off flight path defined in the regulations，the take-off weight corresponding to the standard second segment，extended second segment，and fourth segment obstacle-surmounting method is calculated，and the key factors of maximum take-off weight are analyzed. The obstacle-surmounting margin，climb gradient，and required take-off distance under different obstacle-surmounting methods are calculated. Different distances and gradients are combined to simulate various terrain conditions，and the take-off weights of standard second segment and forth segment obstacle-surmoun-ting mode in those terrain conditions are calculated. The results show that using of fourth segment obstacle-surmounting method can effectively improve the maximum take-off weight of the aircraft in the plateau terrain complex airport. And the larger the gradient of the obstacle is，the more significant the improvement is.